2020
DOI: 10.13106/jafeb.2020.vol7.no8.519
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Citizens’ Satisfaction of E-Government: An Empirical Study in Vietnam

Abstract: This research aims to identify the determinants of e-government satisfaction in Hanoi, Vietnam, and assess their impact. To collect data, we conducted an online questionnaire with citizens living in Hanoi in a time span of five weeks. We received 1,107 responses, divided into three groups: unaware, known, but not used, and used e-government. After leveraging past studies on satisfaction in different contexts, we arrived at six external variables that are of particular relevance to e-government satisfaction (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 28 publications
5
34
0
13
Order By: Relevance
“…The result found that trust in e-government has no effect on user satisfaction. This finding in line with previous studies such as Santa et al (2019), Tegethoff (2019), andNguyen et al (2020). MSME taxpayers who use e-filing do not consider their trust addressed at IDGT website as e-government system, but more focus to online services in general (Santa et al, 2019).…”
Section: The Effect Of Trust In E-government On User Satisfactionsupporting
confidence: 87%
“…The result found that trust in e-government has no effect on user satisfaction. This finding in line with previous studies such as Santa et al (2019), Tegethoff (2019), andNguyen et al (2020). MSME taxpayers who use e-filing do not consider their trust addressed at IDGT website as e-government system, but more focus to online services in general (Santa et al, 2019).…”
Section: The Effect Of Trust In E-government On User Satisfactionsupporting
confidence: 87%
“…Developing and managing a good digital healthcare system is complex (Mathews et al, 2019). In developing a good digital government-based healthcare system in Vietnam, trust and transparency are among the most crucial factors (Nguyen et al, 2020). Indeed, effective communication through Internet channels requires public trust.…”
Section: Discussionmentioning
confidence: 99%
“…Developing and managing a good digital healthcare system is complex (Mathews et al, 2019). In developing a good digital government-based healthcare system in Vietnam, trust and transparency are among the crucial factors (Nguyen et al, 2020). Indeed, effective communication through Internet channels requires public trust.…”
Section: Discussionmentioning
confidence: 99%